A museum for the future heritage: house of Tehran's auction with the neo-vernacular approach. Issue 1 (1st January 2021) - Hashemi, Nima; Mazaherian, Hamed; Emami, Farnaz
ABSTRACT: Museum design has always been influenced by factors such as the building site, culture, politics, economy, etc. The possibility of using the museum as a multifunctional and adaptable building has always been considered by designers, and it is always seen not as a temporary building, but as a standing work for many years. Another aspect of museums, which is perhaps less well known, is the way it interacts with its objects. After the exhibition, the objects are waiting for an unknown destiny. This is perhaps because some under the title of " auction " sought to sell them, trying to prevent them from forgetting. In Iran, this type of collision is very novel and different. The necessary design of the auction as a multi-functional building is undeniable. Further research shows that public spaces can contribute to creating a meaningful context for future heritage and to increasing their influence in societies to provide a context for future developments.